Exploring Entrepreneurial Risk-Taking Among University Students: A Thematic Analysis - Effendi, Pranoto (Yayasan Sinergi Kawula Muda, 2024)
This study explores why university students embark on entrepreneurial risk-taking activity and to gain insight into how they perceive and cope with the risks when they start business ventures. A qualitative case study is conducted with ten university students by examining business undertakings they want to do after graduation. Thematic analysis method is employed to recognize patterns in the data and identify important themes. The findings show that the students have various motivations and resources to initiate entrepreneurial endeavors. The motivations identified here include personal, social, economic and capability reasons; while the resources entail soft and hard skills, marketing skill and also skills from training activities. The students are also capable of identifying several entrepreneurial risks and devising plans to mitigate them. The identified risks relate to personality risk, market and capability risks, decision risk, and also risks from external factors. Whereas the mitigations comprise of improving various aspects of marketing, business decision, product design, and the capabilities in general. The findings of this study have implications for business education to inform the design and scope of entrepreneurial teaching and programs in preparing the students for planning and devising appropriate business strategy, and also for nurturing genuine motivation and equipping them with the precise set of the required skills. Future study should pursue two streams of researches namely, quantitative research for examining more concrete variables relate to entrepreneurial motivation, risk and skill, and also longitudinal research for confirming how the perceived risks previously identified manifesting in real business life.